VALIDITY OF CONTEXTUAL TEACHING AND LEARNING (CTL) COMIC LEARNING MEDIA - Teni Suriani; Andi Kurnia Riski Sanneng (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
The lack of student interest in learning mathematics is caused by the teaching materials used not being able to make students active so that student scores have not reached the Minimum Completeness Criteria (KKM). School teaching materials contain many questions with almost the same level of difficulty and solution methods so that students get a little bored of doing them. This research aims to develop mathematics learning media in the form of comics with Contextual Teaching and Learning (CTL) nuances to improve the mathematics learning outcomes of class VII students at SMP N 20 Jambi City. In this development it is expected to obtain valid mathematics learning media results. This type of research is development research that produces a product in the form of learning comics. The development of this comic uses the ADDIE model which consists of 5 stages, namely the Analyze, Design, Development, Implementation, Evaluation stages. The research subjects were class VII students of SMP N 20 Jambi City. Learning device validation was carried out by mathematics education experts and Indonesian language education experts. The overall validation results for comic media are very valid with a success rate of 85.52%. With this it can be concluded that the development of comic media with Contextual Teaching and Learning (CTL) nuances can be used as teaching material.